How many stroke patients might be eligible for mechanical thrombectomy?. (December 2016) - Tawil, Salwa El; Cheripelli, Bharath; Huang, Xuya; Moreton, Fiona; Kalladka, Dheeraj; MacDougal, Niall JJ; McVerry, Ferghal; Muir, Keith W
Introduction: Recent studies showed improved patient outcomes with endovascular treatment of acute stroke compared to medical care, including IV rtPA, alone. Seven trials have reported results, each using different clinical and imaging criteria for patient selection. We compared eligibility for different trial protocols to estimate the number of patients eligible for treatment. Patients and methods: Patient data were extracted from a single centre database that combined patients recruited to three clinical studies, each of which obtained both CTA and CTP within 6 h of stroke onset. The published inclusion and exclusion criteria of seven intervention trials (MR CLEAN, EXTEND–IA, ESCAPE, SWIFT-PRIME, REVASCAT, THERAPY and THRACE) were applied to determine the proportion that would be eligible for each of these studies. Results: A total of 263 patients was included. Eligibility for IAT in individual trials ranged from 53% to 3% of patients; 17% were eligible for four trials and under 10% for two trials. Only three patients (1%) were eligible for all studies. The most common cause of exclusion was absence of large artery occlusion (LAO) on CTA. When applying simplified criteria requiring an ASPECT score > 6, 16% were eligible for IAT, but potentially 40% of these patients were excluded by perfusion criteria and more than half by common NIHSS thresholds. Conclusion: Around 15% of patients presenting within 6 h of stroke onset were potentially eligible for IAT, but clinical trial eligibility criteria have much more limited overlap than is commonly assumed and only 1% of patients fulfilled criteria for all recent trials.